2009
DOI: 10.1111/j.1365-2133.2009.09594.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic features of acral lentiginous melanoma in a large series of 110 cases in a white population

Abstract: The presence of a parallel-ridge pattern and/or irregular diffuse pigmentation within the lesion is highly indicative of melanoma on volar skin. An irregular lines pattern is the most prominent dermoscopic feature of pigmented ALM of the nail apparatus. Amelanotic ALM either in volar skin or in nail apparatus is characterized by remnants of pigmentation and a polymorphic vascular pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
121
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 21 publications
7
121
1
6
Order By: Relevance
“…In particular, the area, perimeter and diameters (maximum and minimum) were larger. This correlated well with reports in the literature [41,42]. Indeed, in the Saida algorithm, a diameter of PP-PSL greater or less than 7 mm is considered an important cut-off in deciding whether to follow up or remove equivocal lesions [34].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In particular, the area, perimeter and diameters (maximum and minimum) were larger. This correlated well with reports in the literature [41,42]. Indeed, in the Saida algorithm, a diameter of PP-PSL greater or less than 7 mm is considered an important cut-off in deciding whether to follow up or remove equivocal lesions [34].…”
Section: Discussionsupporting
confidence: 74%
“…In this regard, it is worth recalling that many authors have reported a combination of many elements and disorganization in their disposition within a PSL as a dermoscopic feature peculiar to melanoma [20,21,22,23,43,44]. The shape of the edges is undoubtedly another factor that has proved crucial in the differentiation of palmoplantar nevi and palmoplantar melanomas [19,20,41,45]. In fact, the variables related to boundary evenness (variance of border gradient, border homogeneity and border interruptions) showed statistically significant differences between palmoplantar melanoma and nevi.…”
Section: Discussionmentioning
confidence: 99%
“…With 66 acral melanomas this is the largest series on dermoscopy of acral melanoma in a predominantly Caucasian population to date [13,14,15,16]. Eight lesions (3 melanomas) were from Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…17,21 Acral melanomas are located on palms, soles, fingers, toes and in the nail unit. The dermoscopic features of melanomas located on the palms and soles were described Saida et al 22 The two most prevalent features were irregular diffuse pigmentation and the parallel-ridge pattern with a sweat glands infiltration. 22 Presence of the latter feature allows detection of melanoma with the diagnostic 86.4% sensitivity and 99% specificity.…”
Section: 11mentioning
confidence: 99%
“…Approximately 43% of acral melanomas show a combination of three or more types of blood vessels. 22 In the case of acral melanoma of the nail unit, the most prominent pattern is the presence of irregular lines (70%). Nail dystrophy occurs in 43% of cases.…”
Section: 11mentioning
confidence: 99%